A Patriot of Many Homelands, a Mediator, a Translaborator. On Julia Dickstein-Wieleżyńska and her Life with Translation - Kłos, Anita; Wilczak, Mariola (Porównania, 2021)
Julia Dickstein-Wieleżyńska (1881–1943) – a historian of literature and philosophy, poet, publicist, social and educational activist, as well as a translator of fiction and scientific literature from many languages – is still an under-appreciated figure in literary studies. The paper focuses on the general characteristics of Dickstein-Wieleżyńska’s activity as a transcultural mediator and translator, as well as on the role of translation against the background of her numerous interests and activities. Her unpublished correspondence with an anthropologist and historian of religion, Raffaele Pettazzoni (1883–1959), allows to see her translation work in a personal and sociological perspective, as a collaboration or translaboration (Alfer) between various agents of the translation process. Dickstein-Wieleżyńska’s lettersto Pettazzoni also show the limitations encountered by a female intellectual in the literary and scientific world of the first half of the twentieth century.